Copper toxicity assessment in two soil natural with different pH bands - An approach to edaphic plants and organisms Toxicidade do cobre em função da correção do pH em dois solos naturais - Uma abordagem com plantas e organismos edáficos - Zortea T.* (2016)
The growing agricultural development has resulted in environmental problems of the generation of waste containing toxic elements and some inadequate agricultural practices can trigger copper (Cu) accumulation in the soil. The aim is to evaluate the effects of liming on copper toxicity, on the germination of plants and soil biota. Ecotoxicological tests of seed germination were performed, which were used species Avena sativa and Vicia villosa, and avoidance test organisms test species Enchytraeus crypticus, both tests were performed in Oxisol (LVd) and Entisol (RQo). The treatments consisted of increasing doses of copper sulfate (CuSO4), and 0; 10, 40, 80, 160 and 320 mg kg-1 in soil pH corrected and uncorrected. The seeds of exposure A. sativa and V. villosa to increasing doses of CuSO4 expressed no toxic effect on the germination rate (P> 0.05) in both soils, regardless of pH correction. Significant avoidance was observed for LVd on the first dose and evaluated for significant avoidance RQo was also observed, however, with a range of doses according to the pH adjustment. Thus contamination of different types of natural soil with CuSO4 does not affect seed germination rate A. sativa and V. villosa, but leakage was enchytraeids E. crypticus evaluated in both soils (LVD and RQo), indicating that earthworms are able to detect and prevent soil contaminated with Cu.